Animal Healthcare Service Delivery System in Uttar Pradesh State of India: Perception of Government Veterinary Officers - Bardhan, D; Kumar, Sanjay; Singh, Rishi (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was carried out to ascertain the perception of government veterinary officers (GVO’s) towards present status of animal healthcare services (AHS) in the Indian state of Uttar Pradesh. A total of 22 GVO’s were surveyed from all the nine agro-climatic regions of the state. Findings revealed that most limiting supporting factors in AHS are laboratory support, availability of refrigeration facilities and training in post mortem. Most important constraints in delivering of AHS are posting in distant/ marginal areas, lack of infrastructure, and poor pay and incentives. Major factors hindering provision of AHS at farmers’ doorsteps are cases being reported late, farmers’ unwillingness to pay and other administrative and reporting tasks. The findings of the study have provided crucial information to the policy makers regarding the potential of improving AHS in the state. good quality health services – both preventive Animal Health Delivery System (AHDS) plays a crucial role in sustaining the productivity and viability of the livestock sector. India has one of the largest animal health infrastructure and technical expertise in the world with a vast network of over 50,000 veterinary dispensaries and centres, which together employ over 1,00,000 veterinarians and para-veterinary staff. This vast AHDS network however, cannot be equated with high quality of animal health supplies (Ahuja et al., 2003a). However, future growth of the livestock sector will depend crucially on the availability of and curative. Various reforms are now being advocated as a means of overcoming the inherent problems associated with the state AHDS and of improving the overall efficiency. Several studies in the Indian context are available which have analyzed the demand-side perspective, i.e. perception of livestock producers, regarding potential impact of some of such reforms in AHDS (Bardhan, 2010; Pratap et al., 2012 and Bardhan et al., 2014). Although few studies are available in the developing country context on supply-side perspective, i.e. perception of the